2006
DOI: 10.1038/ng1879
|View full text |Cite
|
Sign up to set email alerts
|

iASPP preferentially binds p53 proline-rich region and modulates apoptotic function of codon 72–polymorphic p53

Abstract: iASPP is one of the most evolutionarily conserved inhibitors of p53, whereas ASPP1 and ASPP2 are activators of p53. We show here that, in addition to the DNA-binding domain, the ASPP family members also bind to the proline-rich region of p53, which contains the most common p53 polymorphism at codon 72. Furthermore, the ASPP family members, particularly iASPP, bind to and regulate the activity of p53Pro72 more efficiently than that of p53Arg72. Hence, escape from negative regulation by iASPP is a newly identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
213
3
4

Year Published

2007
2007
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 230 publications
(227 citation statements)
references
References 28 publications
7
213
3
4
Order By: Relevance
“…This finding is in accordance with Mantovani et al (2007) and Bergamaschi et al (2006) We also found the p53 (Arg) (Pro /Arg) variant are higher in the normal subjects. Variation in apoptotic index also correlated with the change in the pattern of Arg/Arg allele in various diseases showing that this allele may prevent the carcinogenic changes by stimulating the Apoptosis in the damaged epithelial cells.…”
Section: Discussionsupporting
confidence: 90%
“…This finding is in accordance with Mantovani et al (2007) and Bergamaschi et al (2006) We also found the p53 (Arg) (Pro /Arg) variant are higher in the normal subjects. Variation in apoptotic index also correlated with the change in the pattern of Arg/Arg allele in various diseases showing that this allele may prevent the carcinogenic changes by stimulating the Apoptosis in the damaged epithelial cells.…”
Section: Discussionsupporting
confidence: 90%
“…Interestingly and importantly, ASPP family members also bind to the prolin rich region of p53 in addition to the DNA binding domain, which displays polymorphic loci at codon 72 in humans ( Figure 6). Bergamaschi et al (2006) described selective regulation of codon 72 variants by ASPP family members, particularly iASPP, bind to and control the activity of p53Pro72 more efficiently than that of p53Arg72, indicating that p53Arg72 activates apoptosis more capably than p53Pro72 due to getaway from negative regulation by iASPP. Hence, the most efficient way to inactivate the apoptotic function of p53Arg72 in human tumorigenesis is by intragenic mutation.…”
Section: Aspps: Interaction With P53mentioning
confidence: 99%
“…The frequency of the allele encoding p53Pro72 is closely linked to latitude and is much higher in populations living near the equator suggesting that p53Pro72 is selected in an environment with high levels of UV light (Sjalander et al, 1995). A novel mechanism by which the ASPP family members selectively regulate the apoptotic function of p53Pro72 and p53Arg72 has been described (Bergamaschi et al, 2006). iASPP has a higher binding affinity to p53Pro72 than to p53Arg72, and preferentially modulates the apoptotic potential of p53Pro72 over p53Arg72.…”
Section: Iaspp Modulates the Apoptotic Function Of P53 Codon 72 Polymmentioning
confidence: 99%